Assessing interventions to increase compliance to patching treatment in children with amblyopia: a systematic review and meta-analysis. Issue 2 (27th November 2015) - Dean, Sarah Elizabeth; Povey, Rachel Clare; Reeves, Jessica
Abstract : Background/Aims: Amblyopia is the most common condition affecting visual acuity in childhood. Left untreated it will not resolve itself, leading to increased risk of blindness. Occluding the good eye with a patch is a highly effective treatment if carried out before age 7 years but compliance is a major problem. This systematic review addresses the question: How effective are existing interventions at increasing compliance to patching treatment in children with amblyopia? Methods: Electronic searches were carried out in June 2014 and updated in April 2015 to identify studies reporting primary data on interventions to increase patching compliance. Data screening, extraction and quality ratings were performed independently by two researchers. Results: Nine papers were included. Interventions including an educational element (5 studies) significantly increased patching compliance and had higher quality ratings than interventions that changed aspects of the patching regime (3 studies) or involved supervised occlusion (1 study). Meta-analysis was conducted on four studies and indicated that overall interventions involving an educational element have a significant small effect r=0.249, p<0.001. Conclusions: Interventions to increase patching compliance should include educational elements. High quality research is needed to further assess the effectiveness of specific elements of educational interventions and additional behaviour change techniques.